Menstural function preservation treatment of a primary vaginal clear cell carcinoma with ovarian transposition and vaginal brachytherapy - Dimitrios-Efthymios Vlachos; Athanasios Protopapas; Georgios Vlachos; Kyrillos Sarris; Maria Sotiropoulou; Maria Terzi; Dimitris Loutradis (Elsevier, 2021)
Early stage vaginal carcinomas are typically treated with radical surgical procedures or radiation therapy. Both modalities impair the reproductive ability of the patients. We hereby report a case of menstrual function preservation in a 24-year-old patient with an early-stage primary vaginal clear cell carcinoma. We treated the patient with intravaginal brachytherapy after appropriate laparoscopic surgical staging and separate transposition of the ovaries and tubes.The patient is now 6 years without any evidence of disease. She reports minor.complaints during sexual intercourse, while her menstruation and hormonic profile are normal.